Case Report: A PD-L1-Positive Patient With Pleomorphic Rhabdomyosarcoma Achieving an Impressive Response to Immunotherapy - Liu, Jiayong; Liu, Peijie; Gong, Fuyu; Tian, Youhui; Zhao, Xiaochen (Frontiers in Immunology, 2022)
There is currently a lack of effective systemic treatment for patients with advanced pleomorphic rhabdomyosarcoma (PRMS). Although programmed death protein 1 (PD-1) inhibitors have shown efficacy in various solid tumors, their effects on PRMS have not been well established. Here, we present a case of a 12-year-old Chinese male adolescent with metastatic PRMS who benefited from the PD-1 inhibitor nivolumab. The patient initially underwent primary tumor resection but failed to respond to subsequent first-line chemotherapy and second-line pazopanib treatment. Pathological examination showed positive PD-L1 expression and tumor-infiltrating lymphocytes in the tumor tissue, and the patient was administered nivolumab as a posterior-line treatment. After attaining a clinically partial response (PR), surgical resection was performed, which was followed by adjuvant nivolumab. At the time of the submission of this manuscript, the patient achieved recurrence-free survival (RFS) lasting 45 months and counting. This is the first clinical evidence that a patient with refractory PRMS was controlled by anti-PD-1 antibody, with an RFS lasting more than three years. This case suggests that PD-L1 expression and T cell infiltration could be used as potential biomarkers for PRMS immunotherapy.